2007
DOI: 10.1097/01.ijg.0000243477.82779.31
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Silicone and Polypropylene Ahmed Glaucoma Valve Implants

Abstract: Silicone and polypropylene AGVs have similar results with respect to both safety and efficacy in the treatment of patients with refractory glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 20 publications
0
15
0
2
Order By: Relevance
“…Ishida et al 10 showed that the mean IOP was significantly lower in silicone valves at 3, 6, and 12 months postoperatively. Conversely, other authors [11][12] could not detect any statistically significant difference in IOP decrease, postoperative antiglaucoma medications, rate of complications, or changes in visual acuity between silicone and polypropylene valves at any follow-up visit.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Ishida et al 10 showed that the mean IOP was significantly lower in silicone valves at 3, 6, and 12 months postoperatively. Conversely, other authors [11][12] could not detect any statistically significant difference in IOP decrease, postoperative antiglaucoma medications, rate of complications, or changes in visual acuity between silicone and polypropylene valves at any follow-up visit.…”
Section: Discussionmentioning
confidence: 81%
“…6 Most clinical studies comparing silicone to polypropylene AGVs have been retrospective studies on adult eyes and showed better or similar results with the silicone AGV. [9][10][11][12][13] In this prospective controlled study, we compared the efficacy and safety of flexible silicone plate and rigid polypropylene plate AGVs in paediatric glaucoma patients with previously failed conventional glaucoma surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Az FP-7 típusú, fl exibilis tányérú Ahmed im plantátummal azonban inferotemporalis implantáció ÖSSZEFOGLALÓ KÖZLEMÉNY esetén is kedvező hosszú távú tapasztalatokkal rendelkezünk. Az Ahmed FP-7 söntöt a nemzetközi irodalom is kedvezőbbnek találta, mint a korábban általunk is gyakran beültetett S-2 modellt [31,32]. Az Ahmed csarnokvíz-elvezető implantátum beültetésének technikai rész-leteit illetően a szakirodalomra utalunk [12,33].…”
Section: Csarnokvíz-elvezető Implantátumokunclassified
“…Brasil 6 compared the silicone and polypropylene AGV implants. This study compared the implantation of an AGV model FP 7 (silicone) or S2 (polypropylene) in uveitic or neovascular glaucoma.…”
Section: Fig 1 : Agv Implant Placement In the Eyementioning
confidence: 99%